STUDENT ELECTRONIC CARD - A NEW APPROACH TO DOCUMENT MANAGEMENT IN HIGHER EDUCATIONAL INSTITUTIONS (World Bulletin of Management and Law, 2022)
The article discusses the possibility of creating a special student electronic card, similar to bank plastic cards. The structure and basic principles of its work are considered. Ways to access student information using a student card are proposed. The cost of the transition of higher educational institutions to student cards is being assessed